Impact of motion correction on reproducibility and spatial variability of quantitative myocardial T2 mapping - Roujol, Sébastien; Weingärtner, Sebastian (Journal of cardiovascular magnetic resonance, 2015)
Background: To evaluate and quantify the impact of a novel image-based motion correction technique in myocardial T2 mapping in terms of measurement reproducibility and spatial variability. Methods: Twelve healthy adult subjects were imaged using breath-hold (BH), free breathing (FB), and free breathing with respiratory navigator gating (FB + NAV) myocardial T2 mapping sequences. Fifty patients referred for clinical CMR were imaged using the FB + NAV sequence. All sequences used a T2 prepared (T2prep) steady-state free precession acquisition. In-plane myocardial motion was corrected using an adaptive registration of varying contrast-weighted images for improved tissue characterization (ARCTIC). DICE similarity coefficient (DSC) and myocardial boundary errors (MBE) were measured to quantify the motion estimation accuracy in healthy subjects. T2 mapping reproducibility and spatial variability were evaluated in healthy subjects using 5 repetitions of the FB + NAV sequence with either 4 or 20 T2prep echo times (TE). Subjective T2 map quality was assessed in patients by an experienced reader using a 4-point scale (1-non diagnostic, 4-excellent). Results: ARCTIC led to increased DSC in BH data (0.85 ± 0.08 vs. 0.90 ± 0.02, p = 0.007), FB data (0.78 ± 0.13 vs. 0.90 ± 0.21, p < 0.001), and FB + NAV data (0.86 ± 0.05 vs. 0.90 ± 0.02, p = 0.002), and reduced MBE in BH data (0.90 ± 0.40 vs. 0.64 ± 0.19 mm, p = 0.005), FB data (1.21 ± 0.65 vs. 0.63 ± 0.10 mm, p < 0.001), and FB + NAV data (0.81 ± 0.21 vs. 0.63 ± 0.08 mm, p < 0.001). Improved reproducibility (4TE: 5.3 ± 2.5 ms vs. 4.0 ± 1.5 ms, p = 0.016; 20TE: 3.9 ± 2.3 ms vs. 2.2 ± 0.5 ms, p = 0.002), reduced spatial variability (4TE: 12.8 ± 3.5 ms vs. 10.3 ± 2.5 ms, p < 0.001; 20TE: 9.7 ± 3.5 ms vs. 7.5 ± 1.4 ms) and improved subjective score of T2 map quality (3.43 ± 0.79 vs. 3.69 ± 0.55, p < 0.001) were obtained using ARCTIC. Conclusions: The ARCTIC technique substantially reduces spatial mis-alignment among T2-weighted images and improves the reproducibility and spatial variability of in-vivo T2 mapping.
Gesehen am 10.01.2018
Im Titel ist "2" tiefgestellt